l-Methionyl-l-tyrosine monohydrate - Sainath Babu; Michelle O. Claville; Frank R. Fronczek; Rao M. Uppu (IUCrData, 2023)
The study of the oxidation of various proteins necessitates scrutiny of the amino acid sequence. Since methionine (Met) and tyrosine (Tyr) are easily oxidized, peptides that contain these amino acids are frequently studied using a variety of oxidation methods, including, but not limited to, pulse radiolysis, electrochemical oxidation, and laser flash photolysis. To date, the oxidation of the Met–Tyr dipeptide is not fully understood. Several investigators have proposed a mechanism of intramolecular electron transfer between the sulfide radical of Met and the Tyr residue. Our elucidation of the structure and absolute configuration of L-Met–L-Tyr monohydrate, C14H20N2O4S·H2O (systematic name: (2S)-2-{[(2S)-2-amino-4-methylsulfanylbutanoyl]amino}-3-(4-hydroxyphenyl)propanoic acid monohydrate) is presented herein and provides information about the zwitterionic nature of the dipeptide. We suspect that the zwitterionic state of the dipeptide and its interaction within the solvent medium may play a major role in the oxidation of the dipeptide. In the crystal, all the potential donor atoms interact via strong N—H...O, C—H...O, O—H...S, and O—H...O hydrogen bonds.